2019
DOI: 10.1177/1071100719849084
|View full text |Cite
|
Sign up to set email alerts
|

Total Ankle Arthroplasty Survival and Risk Factors for Failure

Abstract: Background: Total ankle arthroplasty (TAA) is an increasingly selected treatment for end-stage ankle arthritis; however, failure and revision of the tibial and talar components remains an issue. Although multiple risk factors have been shown to contribute to early component revision, no study has looked at combining such risk factors into a predictive model that could potentially decrease revision rates and improve implant survival. This study aimed to develop a predictive model for TAA failure based on patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 57 publications
0
42
0
3
Order By: Relevance
“…1 It is possible to hypothesize that most PPCs remain underdiagnosed, both because of the frequently used 2D radiographic follow-up postoperatively and because they probably remain clinically latent and asymptomatic until they become large enough to lead to symptoms and implant failure. 15,16,18 The authors acknowledge a number of limitations in this study. First, although the number of cases is significant for TAR, this remains a rather small series in terms of statistics.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is possible to hypothesize that most PPCs remain underdiagnosed, both because of the frequently used 2D radiographic follow-up postoperatively and because they probably remain clinically latent and asymptomatic until they become large enough to lead to symptoms and implant failure. 15,16,18 The authors acknowledge a number of limitations in this study. First, although the number of cases is significant for TAR, this remains a rather small series in terms of statistics.…”
Section: Discussionmentioning
confidence: 99%
“…É possível indicar o procedimento para pacientes com OA grave sem o perfil descrito previamente, mas nesse cenário as taxas de complicações como infecção, deiscência, dor residual, amplitude de movimento reduzida e taxas de reoperação são elevadas. [59][60][61] São contraindicações absolutas à artroplastia total do tornozelo (ATT):…”
Section: Realizar Os Procedimentos Adicionais Quando Necessáriosunclassified
“…As vias de acesso possíveis são via anterior ou lateral transfibular. [59][60][61] Os estudos com ATT revelam melhora clínica e dos escores de dor em até 64% dos casos. A ATT com o uso dos implantes mais modernos mostra taxas de sucesso de 70 a 90% em 10 anos.…”
Section: Realizar Os Procedimentos Adicionais Quando Necessáriosunclassified
See 1 more Smart Citation
“…13 Multiple studies have demonstrated that malalignment at the ankle joint following TAA increases edge-loading forces, which accelerates wear and increases the risk for revision surgery. 6,7,16 Implant survivorship has been shown to decrease substantially when there is greater than 10° deformity in the coronal plane, but success approaches that of TAA performed in anatomically neutral ankles when the deformity is properly corrected. 13,22…”
Section: Introductionmentioning
confidence: 99%